MORAL VALUES IN JODI PICOULT’S NOVEL MY SISTER’S KEEPER - Maisyarah Mitsla; Safitri Hariani (JOURNAL OF LANGUAGE, 2021)
This study deals with a study of moral values in Jodi Picoult’s Novel My Sister’s Keeper, published in 2004. Moral values are human actions in carrying out their life activities. It is raised through the characters in the novel. The purpose of this study is to find out the elements of moral values contained in the novel. The elements are basic moral principles and moral personality attitudes. The theory used to analyze this topic was put forward by Suseno. The qualitative research method is used in this study. It is a research procedure that produces descriptive data in the forms of written words. After doing the research, it is found that two elements of moral values are found in the novel, they are basic moral principles and moral personality attitudes. Basic moral principles cover good attitude and justice. These basic moral principles can be portrayed through the character, Anna. Furthermore, moral personality attitudes include willingness to take responsibility and moral courage. These personality attitudes are also presented when Anna wants to defend her rights.